'Infogeography' of the Complex Image of Places (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2021)
If a ‘geo–graphy’ exists as a graphic representation of the Earth’s places, can it equally exist to express the representation of its phenomena? Considering the sequence of ‘contemporary places’ as coexistence of highly complex interacting scenarios, the question arises on what methods, what languages and what tools can be valid for possible visual restitution. Although a map is not equivalent to the duplicate of the territory it represents, able to understand the complexity of the communicative architecture of its system (Korzybski, in Mori 2014), it is nevertheless the reading model that allows to catch different aspects, matching the multiple levels of understanding of the system itself (Licata 2008). The graphic model in cartographic key is unicum representative, therefore, not only of the objectivity of the place, but also of its transformations in the course of history (Purini 1985), whose variables progressively broken down, interpreted and ‘re–configured’ make the map a designed image. In view of the above, the paper intends to discuss the theme of ‘place’ mapping as a system of real and rhetorical components (Cristallo, Mariani 2019a) that proceed within a historical–evolutionary path: from the first Dada photomontages as ‘interpretative processes’ to the examples of digital photographic compositing of the 2000s, through the photographic Atlases of Memory, up to a reflection on community maps as conceptual synthesis of stratified and self–determined information, in the definition of a visual grammar, by the local communities subject of the mapping. A critical path that naturally ends in the subject of a cartographic representation designed through Information Design strategies that include the graphic and visual ‘shaping’ of compositional–interpretative processes (Ciuccarelli 2014).
Keywords: Information Design; interpretation; mapping